Patterns of Breastfeeding Practices among Mothers in Two Urban Cities in Vietnam - Giang, Hoang Thi Nam; Duy, Do Thi Thuy; Khowaja , Faisal; Minh , Le Huu Nhat; Pham, Hoang Nhat; Hieu, Le Tho Minh; Huy, Nguyen Tien (IIUM Medical Journal Malaysia, 2023)
INTRODUCTION: Breastfeeding is associated with lower risk of child morbidity and mortality and foster overall child development. However, suboptimal breastfeeding practices have been reported in many countries. This study aims to describe patterns of breastfeeding from birth to 24 months in Vietnam and examine factors associated with the maintenance of breastfeeding at 12 months. MATERIALS AND METHODS: 573 mothers whose infants aged from 12 to 24 months in a multi-centre cross-sectional study were recruited. RESULTS: The prevalence of initiation of breastfeeding within the first hour post-partum was 52.9%, between 1 to 24 hours was 21.9%, after the 24 hours was 25.2% and none not initiated by the 7th day after birth. The prevalence of delayed initiation of breastfeeding was significantly higher in caesarean section than in vaginal births (p=0.0001). Prevalence of infants ever breastfed was 100%; exclusively breastfed at 6 months was 19.7%, continued breastfeeding at 12 months was 92.5%, and continued breastfeeding at 20-24 months was 43.5%. There were 16.4% of mothers had breastfeeding problems. Correctly describing the recommended duration of exclusive breastfeeding and not using a bottle to give expressed milk to the infants were factors associated with the higher prevalence of breastfeeding maintenance for 12 months. CONCLUSION: Early initiation of breastfeeding and exclusive breastfeeding prevalence at 6 months in our study earn rating of “good” and “fair” respectively according to World Health Organization (WHO) recommendation. Improving mothers’ knowledge of exclusive breastfeeding recommendations and educating about breast milk expression may improve the prevalence of breastfeeding maintenance at 12 months.